Uprawnienia i obowiązki podmiotu habilitującego w postępowaniu o nadanie stopnia doktora habilitowanego - Szewczyk, Ewa (Studia Prawa Publicznego, 2022)
The issue of awarding academic degrees and titles has been regulated by law in Poland since 1920 and has evolved signiﬁcantly over the course of the century. The promotion procedure, the effect of which is the award of the degree of habilitated doctor, is conducted at individual stages of the ﬁrst-instance procedure by the Council of Scientiﬁc Excellence and the habilitation entity. It is worth bearing in mind that the purpose of this procedure is to issue a decision of great social im-portance, not only for the person concerned, but also for the scientiﬁc community, and even more broadly, for everyone who, as a university student, would like to formally put their knowledge to use. This publication introduces the role of the Scientiﬁc Excellence Council, the habilitation entity and the habilitation committee in this procedure. Within this framework, the entire procedure for awarding the degree of habili-tated doctor (dr hab.) falls within the remit of the habilitation entity. On the other hand, the tasks of the Scientiﬁc Excellence Council include only taking certain actions in the procedure for awarding the habilitation degree. This is because the application for the initiation of the procedure is submitted to this Council, which, having formally assessed it, transfers the application to the habilitation entity. The Council’s participation in the procedure at the stage of the ﬁrst-instance procedure ends with it appointing part of the habilitation committee. The essential role of the Council may be revealed only after the end of the procedure. It is the Coun-cil that hears the case in secondary proceedings, should an appeal be lodged. If a postdoctoral researcher exercises their right to lodge an appeal to the Council of Scientiﬁc Excellence through the postdoctoral entity, this opens up the possibility of exercising a very important right, namely remonstration, which consists in making the self-veriﬁcation of the decision issued by it pursuant to Art. 132 of the Code.